Roles and mechanisms of stem cell in wound healing - Ayavoo, Thurga (Stem Cell Investig, 2021)
Wound healing phases comprise of highly synchronized process that begins due to a damage and restores the integrity of the injured tissues. Wound healing reduces the damage in tissue and supply sufficient oxygen and tissue perfusion, provide proper nourishment and humid wound healing atmosphere to re-establish the essential status of exaggerated parts. The untreated wound becomes susceptible for pus development, bacterial infection and complications like sepsis. Traditional and modern approaches are in practice to treat acute, open and chronic injuries, however, present wound care management has met with challenges and minimal positive effects. Stem cells have possible wound healing capability to overwhelm restrictions of the current wound care practices as it produces faster tissue regeneration in wound repair. Stem cells are unspecialized cells derived from adult body tissues and embryos that differentiate into any cell of an organism and capable of self-regeneration. The understanding on molecular mechanisms of stem cells has become the central and promising field in scientific study. This review focuses on the pre-existing traditional and modern treatments for wound healing, and types and roles of stem cells in wound care management. This review also focuses on the fundamental molecular characterization and factors influencing the molecular mechanisms of stem cells in wound healing.